Courseware For Nondestructive Testing (Penetrant Testing And Magnetic Particle Testing) - Ang , Su Im (UTeM, 2009)
This project is built to develop a courseware for subject Non-destructive Failure Analysis (MIT). NDT is a study case of Material and Structure which is a technique using in manufacturing areas. In this project, scope of courseware content only covered on two chapters out of several chapters of NDT. These two chapters are such as Penetrant Testing and Magnetic Particle Testing. Objective to create a courseware based on Coherence principle in Cognitive theory for Multimedia learning. ASSURE model as the project methodology and the instructional design of this courseware is Coherence Principle based on Cognitive theory. The analysis of project is basically discussed about the project requirement analysis, and the design stage of courseware begins with the preliminary design which is development of storyboard. The Implementation stage is focus on the technically develop of courseware; the production of media elements will wvered the prototype of project testing and evaluation of project will begin after the prototype -finished created, the feedback from user will be needed to continue maintenance of project.